Synthesis, characterisation and electrocatalytic behaviour of three series of Metal Organic Frameworks - Murinzi, Tafadzwa Wendy (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
Metal organic frameworks (MOFs) have received a lot of attention over the past few years due to their vast range of interesting properties and applications, such as catalysis, environmental sensing and storage. This wide range of potential applications is afforded by careful selection and manipulation of the components chosen in assembling of MOFs. In this study, three series of MOFs were synthesized from Co(II), Cu(II) and Mo(VI) polyoxometallates with either 1,3,5-benzenetricarboxylic acid, 1,2,4,5-benzenetetracarboxylic acid or 2,6- pyridinedicarboxylic acid as the ligands. In series 1, the common 1,3,5- benzenetricarboxylic acid MOF, HKUST-1, and POM modified HKUST-1 compounds involving encapsulation and encorporation of the POM were utilised. In series 2, flexible cobalt(II) benzenepolycarboxylate MOFs which investigated the effect of varying the degree of carboxylate substituent were utilised. In series 3, flexibly reduced heterocyclic polycarboxylate MOFs using 2,6-pyridine dicarboxylate were utilised. Solvothermal and slow evaporation synthesis conditions were employed. Where single crystals of good quality were produced, single crystal X-ray diffraction (SC-XRD) was employed for structural elucidation. In the absence of such crystals, a combination of elemental analysis, inductively coupled plasma optical emission spectrometry (ICP-OES) and powder X-ray diffraction (PXRD) was used. Characterization of the MOFs was done by Fourier transform infrared spectrometry (FTIR) and thermal methods, namely thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The electrocatalytic potential of the compounds in the oxidation of L-cysteine was then investigated using a variety of techniques. Cyclic voltammetry was used for L-cysteine detection whilst chronoamperometry and differential pulse voltammetry were used to determine the nanoprobes' sensitivity, rate constants and detection limits. Electrochemical impedence spectroscopy was used to investigate the charge transfer resistance (RCT) and electron transfer kinetics. Of the three, series 3 gave the best signals and sensitivities for electrocatalysis of L-cysteine followed by series 2 and lastly series 1. Series 2 showed the highest stability and series 1 required the least overpotential. The results highlight the effects of different metal centres and ligands on electrocatalysis. The application of MOFs in electrochemistry is a relatively new field making the findings of this study a significant addition to the body of knowledge.
Keywords: Electrochemistry; Metal-organic frameworks; Polyoxometalates; Fourier transform infrared spectroscopy; Electrocatalysis; Cysteine